SATISFACTION AS INTERVENING VARIABLE TO BUILD CUSTOMER’S LOYALTY TOWARDS PT.SAMUDERA PERDANA SELARAS SEMARANG AS FREIGHT FORWARDING COMPANY - Ayu Wular Arum; Budi Prasetya; Sri Eka Sadriatwati (Admisi dan Bisnis, 2018)
This research is purposed to find out whether there was any direct or indirect significant and positive influence between service quality which consist of 5 indicators: reliability, responsiveness, assurance, empathy, and tangible, price, customers’ satisfaction to customers’ loyalty. The population of this research are all exporters of PT.Samudera Perdana Selaras Semarang in 2016 which are 80 exporters. The sample technique used for this research is saturation sample which means all exporters. The analysis technique used was path analysis.The result shows that the F test for regression stage 1 and 2 are higher than F table so it is concluded that there is an influence between Service Quality and Price variable to Exporter’s Satisfaction simultaneously or H3 is accepted, and hypothesis that there is an influence between Service Quality, Price, and Exporter's Satisfaction to Exporter’s Loyalty simultaneously or H7 is also accepted. Partially, based on t test for regression coefficient stage 1 and 2, price is proved to have the biggest influence directly and indirectly to customer loyalty with regression coefficient between 3,485 and 4,362. While the coefficient of determination (R test) is obtained by adjusted R2 value = 0.608 = 60.8% shows that the influence of Service Quality, Price, Exporter's Satisfaction on Exporter’s Loyalty is 60,8%, and the influence of other variables that influence the value of exporter's satisfaction variable beyond this research is 39,2%.It is recommended that PT.Samudera Perdana Selaras Semarang provides services as promised and in accordance with customer’s expectations, also by improving the service quality by 24 hours availibility of services whether there is a change or no change of stuffing or loading and unloading schedule.